Rumpel-Leede Phenomenon Associated with Pneumatic Compression: A Case Report - Ploydaeng M; Jurairattanaporn N; Suchonwanit P; Rattananukrom T (Dove Medical Press, 2022)
Monthanat Ploydaeng, Natthachat Jurairattanaporn, Poonkiat Suchonwanit, Teerapong Rattananukrom Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Teerapong Rattananukrom, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 ext 4, Email teerpongrattananukrom@gmail.comAbstract: Rumpel-Leede phenomenon is a rarely reported condition with an unknown prevalence. It is characterized by the acute development of non-blanchable purpuric macules resulting from dermal capillary rupture caused by compressive forces. We report a case of Rumpel-Leede phenomenon in both feet following the application of pneumatic compression in a 49-year-old woman who underwent en bloc spondylectomy for a giant cell tumor of the spine. The condition appeared after the application of pneumatic compression on both legs for venous thromboembolism prophylaxis, and the lesions spontaneously resolved after discontinuation of compression. Currently, most cases are reported in patients with a history of diabetes mellitus, hypertension, or thrombocytopenia. We report a case of Rumpel-Leede phenomenon in a patient without underlying medical conditions. In our patient, capillary fragility combined with increased intracapillary pressure was hypothesized as the underlying mechanism.Keywords: capillary fragility, capillary leakage, petechiae, thrombocytopenia, tourniquet test, sepsis